The effect of the fluctuations in the components of aggregate demand on the non-oil GDP of the Kingdom of Saudi Arabia: a Vector Auto-Regression analysis - Alquadair, Khalid Hamad A. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
This study investigates the effect of the fluctuations in the components of aggregate demand on the non-oil GDP (RNOGDP) in the Kingdom of Saudi Arabia (KSA) using Vector Auto Regression analysis(VAR). The cointegration test indicates the existence of a long-term relationship between RNOGDP and the components of aggregate demand. The variance decomposition (VD) suggests that fluctuations in real government expenditure (RGOV) and real net exports (RNEXP) play a major role in explaining the fluctuations of real non-oil GDP, while the Impulse Response Functions (IRFs) indicate that the fluctuations in RGOV and real private consumption (RCONS) have a positive and the greatest influence on fluctuations in RNOGDP in the short run, but that vanishes in the long-term. On the other hand, the IRFs indicate that fluctuations in real investment (RI) and RNEXP have a negative effect on the fluctuations in RNOGDP in the short run, though they decline in the long run
Argumenta Oeconomica, 2014, Nr 1 (32), s. 95-113
Keywords: Saudi Arabia; Non-oil GDP components; Vector Auto Regression; variance decomposition; Impulse Response Functions